Development stages horseweed in soybeans competition - Silva,Diecson Ruy Orsolin da (2017)
ABSTRACT: The objective of this study was to evaluate the relative competitive ability of soybean with different development stages of hairy fleabane. Two experiments were conducted in greenhouse, in a completely randomized design. In the experiment it was tested soybean and hairy fleabane competition at different stage of development (rosette and 15 cm height) at the proportions 100:0, 75:25, 50:50, 25:75 and 0:100, and total plant population was 315 plant m-2. The variables evaluated were plant height, leaf area, and shoot dry matter (leaves and stems). Competitive analysis was performed by diagrams and interpreting the competitiveness index. The soybean has greater competitive ability that horseweed for both development stages. The intraspecific competition is more intense for soybean when in hairy fleabane rosette stage, and the competitive relations are equivalent between soybean and hairy fleabane of 15 cm tall. The both hairy fleabane stages were injured in the soybeans competition.